No acceleration of recovery from exercise-induced muscle damage after cold or hot water immersion in women: A randomised controlled trial. - Vanessa Wellauer; Ron Clijsen; Giannina Bianchi; Emilia Riggi; Erich Hohenauer (PLoS ONE, 2025)
Trial registration number NCT04902924 (ClinicalTrials.gov), SNCTP000004468 (Swiss National Clinical Trial Portal).